Academic Challenges Faced by Faculty Members at the World Islamic Sciences & Education University During the Corona Pandemic - Al-Khreisha, Saud Fahhad; AL-Saud, Adab Mubarak (Dirasat: Educational Sciences, 2023)
Objectives: The study aims to reveal the academic challenges faced by faculty members at the World Islamic Sciences and Education University during the Covid-19 pandemic from their own perspective. It intends to evaluate the sudden shift to e-learning due to the pandemic and identify the main problems faced by faculty members. The study will analyze the causes of these problems and propose appropriate solutions. Methods: The study adopts a descriptive survey method using a pre-prepared questionnaire that has been validated for its reliability. The questionnaire consists of 46 items covering four areas. The study was conducted on a sample of 156 faculty members from the academic year 2020-2021. The sample was selected through stratified random sampling, representing 58% of the study community. Results: The study's findings indicate that faculty members faced significant academic challenges during the Covid-19 pandemic. There were no statistically significant differences found at a significance level of α=0.05 when considering gender, specialization, years of experience, and academic rank. Conclusions: The study recommends providing training for faculty members in computer usage, software, and educational platforms. It also suggests ensuring an adequate number of technicians capable of providing technical support and solutions to problems for both faculty members and students. Additionally, the study proposes conducting similar research on Jordanian universities to identify the challenges faced by faculty members in e-learning.